National Early Warning Score 2: transcultural adaptation to Brazilian Portuguese - Ana Paula Amestoy de Oliveira; Janete de Souza Urbanetto; Rita Catalina Aquino Caregnato (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: Cross-cultural adaptation of the National Early Warning Score 2 to Brazilian Portuguese. Methods: A methodological study of a cross-cultural adaptation of a scale, based on the Beaton et al. framework, authorized by the Royal College of Physicians. Judges from nine Brazilian states, nurses and physicians evaluated the semantic, idiomatic, cultural, and conceptual equivalence between the original instrument and the translated versions. The nurses, working in inpatient or emergency units, conducted the pilot test, applying the final version to three case studies. Psychometric tests were used for data analysis: Content Validity Index (CVI), Kappa Coefficient, and Cronbach's Alpha. Results: The adaptation showed a mean CVI of 0.98 and perfect/almost perfect inter-rater agreement, with scores above 0.80. The consistency of the scale was 0.712. Conclusion: The process of cross-cultural adaptation of the scale to Brazilian Portuguese was successful, providing Brazilian professionals with an instrument aligned with patient safety.